Karakteristik Arang Kulit Buah Kakao dan Arang Batang Bambu Terhadap Mutu Briket - Mutiara, Elisa; Hamzah, Faizah; Kharisma Dewi, Yossie (JURNAL AGROINDUSTRI HALAL, 2024)
The purpose of this research is to determine the optimum properties of biodegradable plastic made from banana weevil starch with the addition of straw cellulose as reinforcement. This research was conducted using Completely Randomized Method (CRD) with four treatments and four replications. In this study were the addition of straw cellulose with a ratio of starch and cellulose 1:0; 1:0,5 ; 1:1 and 1:1,5. Tests were carried out on strong tensile strength, elongation at break, biodegradation, swelling and water vapor transmission rate. The data obtained were analyzed statistically using analysis of variance (ANOVA). The addition of straw cellulose had a significant effect on the manufacture of biodegradable plastics. The result were biodegradable plastic increase tensile strength, decreases elongation at break, increase biodegradation and air resistance, reduces the rate of water vapor transmission. Biodegradable plastic with the best treatment is the ratio of starch starch ratio of 1 : 1.5 cellulose. The best result biodegrabable plastic has for tensile strength value of 9.56 MPa, elongation 6.8%, complete biodegradation on day 6, swelling 41.51% and WVTR 0.0156%.